Achievements and future perspectives of embryo transfer technology in pigs. (17th October 2019) - Martinez, Emilio A.; Martinez, Cristina A.; Cambra, Josep M.; Maside, Carolina; Lucas, Xiomara; Vazquez, Jose L.; Vazquez, Juan Maria; Roca, Jordi; Rodriguez‐Martinez, Heriberto; Gil, Maria Antonia; Parrilla, Inmaculada; Cuello, Cristina
Abstract: Commercial embryo transfer (ET) has unprecedented productive and economic implications for the pig sector. However, pig ET has been considered utopian for decades mainly because of the requirements of surgical techniques for embryo collection and embryo deposition into recipients, alongside challenges to preserve embryos. This situation has drastically changed in the last decade since the current technology allows non‐surgical ET and short‐ and long‐term embryo preservation. Here, we provide a brief review of the improvements in porcine ET achieved by our laboratory in the past 20 years. This review includes several aspects of non‐surgical ET technology and different issues affecting ET programmes and embryo preservation systems. The future perspectives of ET technology are also considered. We will refer only to embryos produced in vivo since they are the only type of embryos with possible short‐term use in pig production.